Incidence of conversion from laparoscopic to open cholecystectomy and its associated factors - Al-Shammari, Rafea Jasim Hussein; Al-Khazaali, Sabah Noori Abdulraheem (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy has replaced open cholecystectomy as standard procedure for the treatment of Symptomatic cholelithiasis. Nonetheless, conversion from laparoscopic cholecystectomy to open one is still required in many circumstances. The aim of this study was to determine the main causes of conversion to open in laparoscopic cholecystectomy. Methods: From 1st of January 2010 until the 1st of January 2011 one hundred and fifty patients who had laparoscopic cholecystectomy were prospectively followed at the time of surgery by obtaining a data for the patient’s age, sex, time from the introduction of laparoscopic ports till decision of conversion and the cause of conversion if present. Results: Put of the 150 laparoscopic cholecystectomy 9 conversions occurred (the percentage of conversion was 6%). The most common causes were: vascular injuries: 2 patients, empyema of the gall bladder: 2 patients, severe obesity: 1 patient, abnormal position of gall bladder: 1 patient, and dense adhesions and disturbed anatomy: 3 patients. Three patients of conversions are males from 25 male patients underwent laparoscopic cholecystectomy, 6 cases are females from 125 female patients underwent laparoscopic cholecystectomy so the percentage of conversion for male patients is 12% while for female patients is 4.8%. Conclusions: The overall conversion rate in this study was 6% and the most common cause for conversion is dense adhesions, followed by empyema of GB. and severe bleeding that need conversion, and the rate for conversion was higher in male patients.